A Conceptual Model for a Blended Intervention Approach to Support Early Language and Social-Emotional Development in Toddler Classrooms. Issue 1 (January 2023) - Cunningham, Jennifer E.; Chow, Jason C.; Meeker, Kathleen Artman; Taylor, Abby; Hemmeter, Mary Louise; Kaiser, Ann P.
Abstract : The purpose of this article is to present a theory-driven blended intervention model that integrates evidence-based interventions to support language and social development of young children. We (1) provide an overview of practices that are designed to support language and social-emotional development, (2) present a theory of change model that outlines the theoretical basis for our proposed approach, and (3) provide an example of the conceptual model via the blending of Tier 1 interventions that provide class-wide language and behavioral support for young children. We conclude by arguing for the parsimony that a proactive synergy between social and language interventions blended into a single professional development approach will provide.